Research on Optimization of Key Parts of Nuclear Reactor Based on Finite Element Simulation. Issue 3 (January 2021) - Yang, Bo; Yu, Tianda; Deng, Qiang; Chen, Cong; Zhang, Fengshou
Abstract: In view of the higher technical requirements of the third generation PWR for the control rod drive mechanism (CRDM), China's third generation nuclear reactor CRDM hook parts are designed to multi-tooth hook with wear-resistant surfacing. The surfacing welding process is simulated and optimized based on finite element simulation, and reasonable welding process and parameters are determined by simulation results in this paper.According to the optimized welding process, the parts are trial-produced, and the parts of the hook are subjected to metallographic inspection, hardness test and thermal life test. The results show that the optimized hook parts have high hardness and wear resistance, and meet the requirements of the third generation PWR nuclear power plant.